Pengaruh Variabel Makroekonomi dan Indeks Harga Saham Luar Negeri Terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia (BEI) - SUBASTINE , YULIANA (2011)
Capital market is one of the current economic instruments that have evolved rapidly. Measure the performance of capital market is a stock index. The factors can affect the stock index, such as domestic interest rates, foreign exchange rates, international economic conditions, the country's economic cycle, inflate ion rates, tax regulations, the amount of money in circulation. The purpose of this study was to analyze the effect of Interest Rates, Inflations, Exchange Rate of Rupiah, Money Supply, Dow Jones Index variable for the volatility of IHSG in BEI (Bursa Efek Indonesia). The method used multiple linier regression analysis. After that, we must do a classical assumption test in order to make sure that the regression equation is BLUE (Best, Linear, Unbiased, Estimator). In addition, to assess the goodness of fit from a model, we use coefficient of determination test, F test and t test. The data for this research were a monthly data from 2007 - 2010 for each variable. The results of this study indicate that the SBI Interest Rates, and Rupiah Exchange rate were negative ly affected by IHSG. While the variables inflations, money supply and Dow Jones Indeks had a positive effect on IHSG. For the F test, that's all the independent variable affected the IHSG.